2018
DOI: 10.4070/kcj.2017.0359
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Characteristics, and Clinical Outcomes of Patients Undergoing Percutaneous Coronary Intervention in Korea between 2011 and 2015

Abstract: Background and ObjectivesWe sought to evaluate nationwide trends, characteristics, and clinical outcomes in patients undergoing percutaneous coronary intervention (PCI) in Korea.MethodsFrom National Health Insurance claims data in Korea, 81,115 patients, who underwent PCI for the first episode of coronary artery disease between 2011 and 2015, were enrolled. Patients were categorized into angina (n=49,288) or acute myocardial infarction (AMI, n=31,887) groups and analyzed.ResultsThe mean age of patients was 64.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…Another result that may find an answer in the organization of health policies in our country, instead of representing improvement of cardiovascular prevention actions, was the progressive reduction of patients with STEMI and, consequently, of primary PCI during the course of the study. A drop in PCI in acute MI patients was also described in the registry by Han et al 13 Angiographic complexity, with more type B 2 /C lesions, was greater in the period analyzed, and was mostly due to increasingly longer lesions, reflecting the progressive use of longer and small caliber stents. It is worth mentioning that longer stents have become more available in Brazil in Results expressed as n (%).…”
Section: Journal Of Transcatheter Interventionssupporting
confidence: 55%
See 1 more Smart Citation
“…Another result that may find an answer in the organization of health policies in our country, instead of representing improvement of cardiovascular prevention actions, was the progressive reduction of patients with STEMI and, consequently, of primary PCI during the course of the study. A drop in PCI in acute MI patients was also described in the registry by Han et al 13 Angiographic complexity, with more type B 2 /C lesions, was greater in the period analyzed, and was mostly due to increasingly longer lesions, reflecting the progressive use of longer and small caliber stents. It is worth mentioning that longer stents have become more available in Brazil in Results expressed as n (%).…”
Section: Journal Of Transcatheter Interventionssupporting
confidence: 55%
“…12 This fact was also found in a large, more recent (2011 to 2015) Korean registry, with 37% diabetic patients, and a mean mortality of 2.6%. 13 Despite the complexity of these patients and the low mortality rate, the beginning of the period studied demonstrates a bias in patient selection, that is, the multivessel patients with greater angiographic complexity were referred for surgical treatment. [14][15][16] This management is corroborated by the non-availability of drug-eluting stents for patients of the Brazilian Public Health System (SUS) in the period studied, justifying the low rate of use of these devices in this population, despite the growth of their use from 30% to 40% within 10 years.…”
Section: Journal Of Transcatheter Interventionsmentioning
confidence: 99%
“…The number of patients increased by 8% during the period 2011 to 2015 and shows a steadily increasing trend. Correspondingly, with 178 centers in 2015, there was an increase of 17% in the number of centers capable of performing PCI from 2011 [7]. Since medical disputes related to CAG and PCI may well increase in the future, interventional cardiologists may not be able to completely avoid medical disputes during their careers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent westernization has influenced lifestyle, diet, and disease patterns in Korea. In this aspect, Han et al 5) provided valuable evidence of the national trend for PCI in Korea.…”
mentioning
confidence: 99%
“…The authors 5) reported a large nationwide data showing the current practice of PCI in patients with angina pectoris and acute myocardial infarction (AMI) in Korea, and they have well summarized current trends, characteristics, and clinical outcomes of PCI in Korea between 2011 and 2015. This study showed that comorbidities such as hyperlipidemia increased in patients with angina pectoris and AMI from 2011–2012 to 2014–2015.…”
mentioning
confidence: 99%